Uso de herramienta interactiva Liveworksheets en el mejoramiento de la comprensión de textos escritos en inglés en estudiantes de segundo grado de secundaria en la Institución Educativa Maynas 2023 - Cabezas Loayza, Helaman Spencer (2024)
The objective of this research study was to assess the effectiveness of the educational program of the use of the interactive liveworksheets tool to improve second grade students’ reading comprehension in English at Maynas secondary school in Iquitos 2023.The research type was evaluative, with field study, contemporary transectional, univariate and quasi-experimental designs with pre test, post-test of the experimental and control group. The study population was made up by 408 students, with a non-probabilistic sample of 57 divided into two groups: control (28) and experimental (29). The data gathering tool was a valid and reliable written comprehension test. Results In the post test reveal that the experimental group students’ reading comprehension mean score in English was higher than in the control group (10.6 > 7.3). Similarly, in its dimensions: Getting information (11.6 > 7.9), inferencing and interpretating information (7.0>5.6) evaluation of content, context and format (5.6 < 10.9). In conclusion, the study hypothesis was no accepted, since the application of the educational program of the use of the interactive liveworksheets tool no improved significantly the study population students’ reading comprehension in English. (p-value = 0,978> α = 0,05).